2010
DOI: 10.1152/ajpregu.00789.2009
|View full text |Cite
|
Sign up to set email alerts
|

Diversified cardiovascular actions of six homologous natriuretic peptides (ANP, BNP, VNP, CNP1, CNP3, and CNP4) in conscious eels

Abstract: The natriuretic peptide (NP) family consists of seven paralogs [atrial NP (ANP), brain NP (BNP), ventricular NP (VNP), and C-type NP 1-4 (CNP1-4)] in teleosts, but relative biological activity of the seven NPs has not been comprehensively examined using homologous peptides. In this study, we newly identified CNP3 and CNP4 in eels to use homologous peptides, but the CNP2 gene may have been silenced in this species. The CNP4 gene was expressed exclusively in the brain as CNP1, but the CNP3 gene, from which cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…A similar decrease in CNP efficacy compared with ANP, BNP and VNP has been observed in the eel cardiovascular system (Nobata et al, 2010), and this may be indicative of a generally lower CNP efficacy in fish. We also showed that rat ANP infusion into trout significantly increased unstressed blood volume and increased vascular compliance (Olson et al, 1997).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A similar decrease in CNP efficacy compared with ANP, BNP and VNP has been observed in the eel cardiovascular system (Nobata et al, 2010), and this may be indicative of a generally lower CNP efficacy in fish. We also showed that rat ANP infusion into trout significantly increased unstressed blood volume and increased vascular compliance (Olson et al, 1997).…”
Section: Discussionsupporting
confidence: 63%
“…These hormones are produced as pro-peptides and, following cleavage to their mature state, assume a disulfide-linked 17 amino acid ring structure with amino-and carboxy-terminal extensions of variable length. CNP, which lacks the carboxy-terminal extension, is widely considered the ancestral NP (Inoue et al, 2003a), and has been identified in multiple variant forms known as CNP1-4 in medaka, pufferfish and eel (Inoue et al, 2003a;Kawakoshi et al, 2004;Nobata et al, 2010). CNP is found in taxa from agnathans to humans, and appears to be ubiquitously expressed in the central nervous system, and to a lesser extent in the atrium (Arimura et al, 1991;Inoue et al, 2003b;Johnson and Olson, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that BNP administration affects only ghrelin and not PYY speaks against a possible mediation of BNP effects via the cholinergic system. This hypothesis is supported by a physiological study in eels revealing that BNP effects are dependent on β-adrenergic blockade but not on cholinergic blockade (20). The fact that BNP does not influence GLP-1, oxyntomodulin, and PP is somewhat expected in this fasting study, as all these peptides are mainly modulated in response to food intake.…”
Section: Discussionmentioning
confidence: 73%
“…Speculatively, this may be due to atrial natriuretic peptide (ANP), which is present in the testudine heart ( 65 ). In mammals and reptiles, ANP is released by cardiomyocytes in response to pressure or volume induced myocardial stretch and has systemic vasodilatory action ( 41 , 49 ); however, it is unclear if the action of ANP is blunted by cold temperatures like some other endocrine functions ( 45 ). Vasodilation is consistent with previous studies that show arterial hypotension following cold acclimation when animals are studied at their acclimation temperatures ( 27 ).…”
Section: Discussionmentioning
confidence: 99%